Phase III, randomized, double-blind, placebo-controlled clinical study: a study on the safety and clinical efficacy of AZVUDINE in moderate COVID-19 patients - de Souza, Sávio Bastos; Cabral, Paula Gebe Abreu; da Silva, Renato Martins; Arruda, Raul Ferraz; Cabral, Sheila Passos de Figueiredo; de Assis, Arícia Leone Evangelista Monteiro; Viana Junior, Antônio Brazil; Degrave, Wim Maurits Sylvain; Moreira, Aline dos Santos; Silva, Cléber Glória; Chang, Junbiao; Lei, Pingsheng (Frontiers in Medicine, 2023)
Background: In 2019, a highly pathogenic coronavirus named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) surfaced and resulted in the outbreak of coronavirus disease 2019 (COVID-19). With the aim of finding effective drugs to fight against the disease, several trials have been conducted since COVID-19 is deemed treatable only after the availability of antivirals. AZVUDINE (FNC), initially developed for treating HIV, is a potential treatment for COVID-19 as it has the capability to lower the patient's viral load and promote recovery. Methods: Volunteers infected with SARS-CoV-2 confirmed by RT-PCR, with good kidney and liver function, who were not using other antivirals or monoclonal antibodies were eligible. Samples from patients were assessed for viral load every 48 hours during treatment using RT-qPCR and ddPCR. Results: The study's primary outcome measure is the percentage of participants showing an improvement in clinical scores, while the secondary outcome measure is the percentage of participants with a clinical outcome of cure. These measures are used to assess the safety and efficacy of FNC for treating COVID-19. In the analysis of sociodemographic variables, no significant differences were detected between patients in the FNC and the PLACEBO group for race, age group, or sex, with a predominance of 58% for men. The results show a potential benefit to participants who received FNC during the study, as observed in the shorter hospital stay, shorter negative conversion time of SARS-CoV-2, and a significant reduction in viral load. Furthermore, the reduction in fever and chills are significant in D1, D2, and D3. In this study, a total of 112 adverse events cases were noted, with 105 cases being categorized as non-serious and only 7 cases as serious adverse events. Conclusion: The pandemic is not being effectively controlled and is causing multiple waves of infection that require extensive medical resources. However, FNC has demonstrated the potential to reduce the treatment duration of moderate COVID-19 cases, thereby saving significant medical resources. This makes FNC a promising candidate for COVID-19 treatment.